Mechanism of Optical Rotation of Amino Acids Using Electronic State Calculation. Issue 1 (April 2020) - Katsumoto, Shuichi; Mimura, Manami; Ishii, Tomohiko; Sakane, Genta; Ogasawara, Kazuyoshi
Abstract: Because of the chiral nature of the building blocks of living matter, an optical phenomena associated with the chirality constitute an important topic in physical chemistry. The specific optical rotation, which is a parameter for the characterization of the natural optical activity, depends strongly on the conformation of the molecule. In this study, we investigated the dependence of the optical rotation on a molecular conformation in the gas phase by calculating the electronic states of seven kind of chiral amino acids using the DV-Xα method. As a result, we can confirm the existence of an antibonding orbital on the side chain and the optical rotations are strongly related.